Penyuluhan Pemanfaatan Tanaman Obat Keluarga: Daun Ketepeng Cina sebagai Salep Herbal untuk Peradangan Ringan - Aulia, Indriati; Rindayani, Mila Febrina; Tambunan, Lili Yuliana (Jurnal Masyarakat Indonesia (Jumas), 2025)
One of the Indonesian plants that can be used as medicine is the dicotyledonous plant Cassia alata L., commonly known as Chinese ketepeng. Chinese ketepeng (Cassia alata L.) is a member of the Fabaceae family. Chinese ketepeng is traditionally used to treat gastrointestinal disorders, skin diseases, allergic reactions, internal and external infections, and inflammatory conditions. This plant is a popular herbal medicine in natural anti-diabetic treatment in Africa. This extension aims to formulate Chinese ketepeng leaf extract (Cassia alata L.) into an ointment and test the effect of Chinese ketepeng leaf ethanol extract on inflammation in the paws of white rats, using 1% (w/v). Carrageenan solution as an inflammation inducer, with a dose of 0.1 ml every 60 minutes for 6 hours. Changes in the volume of the rat's paw pads were observed using a plethysmometer. Chinese ketepeng leaf ointment extract was given in three doses: 5 mg/kgBW, 10 mg/kgBW, and 15 mg/kgBW. The negative comparator used was the ointment base without the extract, and the positive comparator used was 1% hydrocortisone acetate ointment. The chemical composition of the extract showed the presence of alkaloids, flavonoids, saponins, steroids, and tannins, which are effective in inhibiting the cyclooxygenase pathway, which can inhibit inflammation. Data on the percentage of edema inhibition were analyzed statistically using the Statistical Package for the Social Sciences (SPSS). The results of the extension showed that Chinese ketepeng leaf extract (Cassia alata L.) can be formulated as an ointment. The best anti-inflammatory effect was achieved from the three doses.